Embryonal tumors in the WHO CNS5 classification: A Review - Francesca Gianno; Evelina Miele; Manila Antonelli; Felice Giangaspero (Wolters Kluwer Medknow Publications, 2022)
Embryonal tumors are a heterogenous group of neoplasms mostly defined by recurrent genetic driver events. They have been, previously, broadly classified as either medulloblastoma or supratentorial primitive neuroectodermal tumors (PNETs). However, the application of DNA methylation/gene expression profiling in large series of neoplasms histologically defined as PNET, revealed tumors, which showed genetic events associated with glial tumors. These findings led to the definitive removal of the term "PNET" in the 2016 World Health Organization (WHO) classification of CNS tumors. Moreover, further studies on a large scale of methylation profiling have allowed the identification of new molecular-defined entities and have largely influenced the 5th edition of the WHO classification of CNS tumors (WHO CNS5) for both medulloblastomas and other CNS embryonal tumors. The importance of molecular characteristics in CNS embryonal tumors is well represented by the identification of different molecular groups and subgroups in medulloblastoma. So, in the CNS5, the emerged group 3 and group 4 belong to the classification, and the four molecular and morphologic types are now combined into a unique section. Among other embryonal tumors, two new recognized entities are introduced in CNS5: CNS neuroblastoma, FOXR2-activated, and CNS tumor with BCOR internal tandem duplication (ITD). Embryonal tumor with multilayered rosettes (ETMR), already present in the previous classification now has a revised nomenclature as a result of the new DICER1 alteration, additional to the formerly known C19MC. Regarding atypical teratoid/rhabdoid tumor (AT/RT), three molecular subgroups are recognized in CNS5. The combination of histopathological and molecular features reflects the complexity of all these tumors and gives critical information in terms of prognosis and therapy. This encourages the use of a layered diagnostic report with the integrated diagnosis at the top, succeeded by layers including the histological, molecular, and other essential details.